2016
DOI: 10.3389/fendo.2016.00147
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zn/Cu Ratio Is Associated with Renal Function, Glycemic Control, and Metabolic Parameters in Japanese Patients with and without Type 2 Diabetes: A Cross-sectional Study

Abstract: BackgroundZinc (Zn) and copper (Cu) may play a pivotal role in the pathogenesis of diabetes and diabetic complications by mediating oxidative stress. Both Zn deficiency and excess of Cu are associated with an increased risk of type 2 diabetes and cardiovascular disease. We aimed to investigate the relationships between serum Zn/Cu ratio and glycemic status, renal function, and metabolic parameters in patients with and without type 2 diabetes.MethodsWe conducted a cross-sectional study on 355 subjects (149 type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…This suggests that the Zn 2+ /Cu 2+ ratio reflects the transition from the hypertension phase to T2DM-associated hypertension [33]. In agreement with these observations, a higher Zn 2+ /Cu 2+ ratio has been associated with a reduced risk of poor glycemic control in T2DM patients [102]. Oral administration of zinc together with acetylsalicylic acid to T2DM rats reduces plasma glucose levels and prevents diabetic cardiomyopathy [103].…”
Section: Biometals In Metabolic Disordersmentioning
confidence: 80%
“…This suggests that the Zn 2+ /Cu 2+ ratio reflects the transition from the hypertension phase to T2DM-associated hypertension [33]. In agreement with these observations, a higher Zn 2+ /Cu 2+ ratio has been associated with a reduced risk of poor glycemic control in T2DM patients [102]. Oral administration of zinc together with acetylsalicylic acid to T2DM rats reduces plasma glucose levels and prevents diabetic cardiomyopathy [103].…”
Section: Biometals In Metabolic Disordersmentioning
confidence: 80%
“…We reported that the serum Zn/Cu ratio was positively associated with glycemic control in patients with type 2 diabetes [3]. In another study, patients with type 2 diabetes demonstrated lower handgrip strength, which is a useful predictor of the risk of cardiovascular disease and mortality [4], than those without diabetes [5].…”
Section: To the Editormentioning
confidence: 90%
“…Mocchegiani et al [6] reported an unfavorable association of the serum Cu/Zn ratio with physical parameters, including handgrip strength and mortality, in elderly subjects. Although serum levels of Zn and Cu are influenced by numerous factors, such as the nutritional status and comorbidities [3,6], an adequate Zn/Cu ratio has the potential to ameliorate glycemic control and improve physical functions. However, this is a small-scale, retrospective, observational study; thus, further investigations are needed to understand both the effect of serum Zn/Cu ratio on glycemic control and its underlying mechanism of action.…”
mentioning
confidence: 99%
“…Patients with low serum zinc concentration had a higher risk for death from CHD than patients with high serum zinc level (Figure 1). More recent studies diabetic patients from Iraq, China and Japan also confirmed that lower serum zinc level in T2D patients was related to higher prevalence of diabetic microvascular complications, and represented as an independent risk factor for diabetic nephropathy [11][12][13]. Patients with lower zinc level were more likely to have a longer duration of diabetes, poorer glucose control and worse β cell function [12].…”
Section: Introductionmentioning
confidence: 91%
“…Advancing diabetic nephropathy represented by decreasing GFR and increasing microalbuminuria is associated with lower serum zinc levels [11]. Low serum zinc to copper ratio was positively associated with renal dysfunction in all subjects and poor glycemic control in patients with T2D [13].…”
Section: Introductionmentioning
confidence: 94%